An Essay on Exit Scenarios from the Housing Precarity Feeding Middle Class Homelessness Fears - Meriç Kırmızı (İstanbul Üniversitesi Sosyoloji Dergisi)
In the increasingly precarious atmosphere of today’s neoliberal society, the issue of housing, as a fundamental human right, is becoming precarious in a way that includes the middle classes. This study addresses the problem of housing precarity and homelessness among the middle class, little studied in urban studies and, mostly presented as a success story. The study examines the structural changes that are at the root of these problems and the ways out of them. The issue of housing insecurity as a precondition for homelessness, understood as a social process with its before and after, is presented through a detailed literature review and thematic document analysis. The study, based on an analysis of 82 national and international documents collected under the keywords housing precarity, middle class and homelessness, first defines in detail the problems of housing precarity and homelessness of the middle class and then looks for types of housing that offer alternatives to the precarious housing market. The next section discusses the gaps and contradictions in the literature on housing alternatives and offers theoretical and empirical alternatives. For example, house sharing, which is presented as an alternative in some studies, is criticized as a product of the system in others. This study contributes by pointing to the potential of concepts of the urban commons, the feminist city and social infrastructure as supporting mechanisms in the search for alternative housing. Finally, the paper presents proposals to address the problems of housing precarity and homelessness that also affect the middle class in Türkiye.